UNDERSTANDING BARRIERS TO DIGITAL TRANSFORMATION IN MADRASAH: A CASE STUDY ON INFRASTRUCTURE, DIGITAL COMPETENCE, AND SERVICE QUALITY - Muhammad Munawir Pohan; Wasehudin Wasehudin; Samsu Samsu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Digital transformation is a strategic necessity for madrasas to improve the effectiveness of governance, learning, and the quality of educational services. However, its implementation still faces various obstacles that affect the overall success of digitalization. This study aims to identify and analyze obstacles to digital transformation, focusing on digital infrastructure, human resource digital competence, and the quality of educational services. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation studies with madrasah principals, teachers, education personnel, operators, and students. Data analysis used an interactive model that included data condensation, data presentation, triangulation of sources and techniques, and member checking. The results show that limited digital infrastructure, low digital competence of teachers and education personnel, and the dominance of an administrative orientation in digitalization are the main obstacles to digital transformation. Furthermore, the integration of Islamic values into digital learning content remains suboptimal, thereby hindering substantive improvement in the quality of educational services. This research offers a new perspective: digital transformation in madrasas must be understood as the integration of technological, human resource, and educational service capacities within a human-centered and value-based framework. These findings have implications for developing digital transformation policies that are more adaptive, sustainable, and oriented toward improving the quality of educational services.